Perceptions and understandings of pregnancy, antenatal care and postpartum care among rural Lao women and their families - Sychareun, Vanphanom (BMC Pregnancy Childbirth, 2016)
BACKGROUND: Lao People’s Democratic Republic (Lao PDR) has the highest maternal mortality rate (MMR) and infant mortality rate (IMR) due to traditional practice and beliefs on pregnancy, delivery and postpartum. The objective of this study was to get a better understanding of cultural beliefs and practices surrounding pregnancy, ANC and postpartum care among rural women in Lao PDR. METHODS: Eight focus group discussions and 52 interviews were carried out with delivered women, husbands, mothers, traditional birth attendants, head villagers, Lao Women’s Union members and healthcare workers, in Khammouane and Champasack provinces in Lao PDR. In order to accurately grasp participants’ perceptions and understandings, content analysis was used to analyze the transcripts. RESULTS: Most women in the study claimed to have attended ANC, but participants also explained that it was unnecessary to attend ANC and give birth at a clinic if the woman felt healthy. Factors that discouraged ANC attendance and giving birth at clinics included: time and money constraints; the perceived necessity of giving birth on a “hot bed”; the need for “mother-roasting” after giving birth; the belief that preparing for a birth was a bad omen for the birth; the belief that colostrum is unhealthy for the newborn child; and the preference for cutting the umbilical cord with a piece of sharpened bamboo. CONCLUSIONS: Harmful cultural practices such as discarding colostrum should be discouraged; beneficial practices such as family involvement in birthing and keeping a mother warm after birth could be integrated into biomedical practice. Given the prevalence and importance of the cultural understandings we have described in this study, it is clear that proposed changes in cultural practices need to be addressed with sensitivity and that community stakeholders and trusted leaders will need to be involved.